Evaluation of Elaj Irrigation Project in Babil Governorate - Montader AL Mosawi; Hayder Al Thamiry (Journal of Engineering, 2022)
Climate change causes water shortage (water scarcity) in addition to the dams built by neighboring countries, which caused a lack of Iraq's water share. Therefore, evaluating the irrigation system requires considering its suitability, adequacy, and efficiency. Irrigation is considered adequate when it maintains water availability within the root zone, and if the amount to be added is determined, irrigation efficiency becomes possible by avoiding water loss. Babil Governorate is considered one of the agricultural governorates in the country that depends on its irrigation from Shatt Al-Hilla. The study area is the Elaj project. Three fields were selected for the project (B1, B2, and B3). These fields are located at the project's beginning, middle and end. The evaluation was based on the field measurements of water contents before and after watering during the growing season. Also, the root zone of each plant during the growing season is measured to give more accurate calculations. Accordingly, application efficiency, conveyance efficiency, distribution efficiency, storage efficiency, water productivity efficiency, and water use efficiency were calculated in the project. The application efficiency for the selected fields ranged between (33 to 39) % in B1, (32 to 38) % in B2, and (32 to 39) % in B3. The application efficiency in all fields increased by about 6% during the third watering period between (22/3/2021 to 4/4/2021) due to the low water level in Shatt Al-Hilla during maintenance work that lasted more than a month. The efficiency of the scheme [ηs%] in the project is 32.3%. This value is low and reflects the reality of irrigation in the Babil. Therefore, improvements must be made to the irrigation system.